THE IMPACT OF MOBILE-ASSISTED INTENSIVE READING ON EFL STUDENTS’ MOTIVATION AND READING FLUENCY - Estika Satriani; Miranti Eka Putri; Yulianto Yulianto (JEE (Journal of English Education), 2026)
This study inspects the impact of Mobile-Assisted Intensive Reading (MAIR) on the motivation and reading fluency of EFL students. The study used a quasi-experimental approach that consisted of an experimental and a control group. A questionnaire was used to assess students' motivation and reading fluency. The result of analysis data showed both motivation and reading fluency increasing score compared to the control group. Statistical analysis showed that the average motivation scores were from 68.45 to 82.30, while the reading fluency scores increased from 72.10 to 85.75 after the implementation of MAIR. In contrast, the control group showed only slight improvements, with the motivation score from 69.10 to 72.15, and reading fluency from 71.85 to 74.20. The MANOVA results revealed a statistically significant difference between the experimental and control groups on the combined dependent variables, F(2, 57) = 38.75, p < 0.001, Wilks’ Λ = 0.421. The effect size (Partial η² = 0.579) indicates a large effect, suggesting that the treatment had a substantial impact. Besides that, MAIR had a significant effect on students’ motivation (p < 0.001). MAIR also had a significant effect on reading fluency (p < 0.001). Both variables confirm the effectiveness of the treatment. These findings suggest that MAIR fosters a more engaging learning environment, encourages learner independence, and allows for repeated interaction with the text, all of which are important for improving EFL students' reading fluency. Future researchers are advised to explore long-term impact of MAIR on students' reading comprehension, vocabulary growth, motivation, and reading fluency..